The Impact of Routine Chlamydia trachomatis (CT) Screening during Pregnancy on the Seroepidemiology of Chlamydial Infection in Children, 1991–2015. (4th October 2017) - Banniettis, Natalie; Wisecup, Kimberly; Byland, Leah; Watanabe, Izumi; Clement, Sheinese; Hammerschlag, Margaret; Kohlhoff, Stephan
Abstract: Background: CT remains the most prevalent STI in developed and developing countries.Prenatal screening and treatment of pregnant women has resulted in a dramatic decrease of perinatal CT infection. There have been limited seroepidemiologic studies in unselected children and adolescents following the implementation of routine CT screening as first recommended by the CDC in 1993. Methods: Anonymized banked sera (-80°C) and prospectively collected sera from children and adolescents in Brooklyn, NY, were tested for anti-CT IgG via a validated enzyme immunoassay. Serum samples were divided by collection years: Group 1 (1991–1995, prescreening) and Group 2 (2012–2015, post-screening). Infants <1 year of age were excluded due to interference of maternal antibody. Maternal screening and CT infection rates during pregnancy were determined via a retrospective review of 200 random charts (2016–2017). Statistical analysis by Fisher's exact test. Results: 297 serum samples were identified (age range 1–20 years). 18.5% (10/54) of subjects ≤10 years of age in Group 1 tested positive for anti-CT IgG, while none tested positive in Group 2 (0/55), P = .0006. Children >10 years had a prevalence of 10.3% (3/29) in Group 1 and 7.5% (12/159) in Group 2, P = .7. Maternal screening rate was estimated at 95.5%, with 100% screened if <25 years of age. The rate of maternal CT infection during pregnancy was 4.5% (9/200) overall, 8% (4/49) in <25 year olds and 3.3% (5/151) in ≥25 year olds. Conclusion: Children ≤10 years of age in the prescreening group (1991–1995) had relatively high rates of seropositivity, likely due to persistence of antibody from perinatal infection. The absence of CT antibody in children ≤10 years of age in the post-screening group (2012–2015) and the high rate of prenatal screening (>95%) in this high-risk population suggest prenatal screening and treatment of pregnant women has been effective at preventing perinatal CT infection. Disclosures: All authors: No reported disclosures.